Influence of Acute Mental Arithmetic Stress on Taste and Pungency - OSHIMA, Tatsuhiro; FUJIKAWA, Tetsuya; BANNAI, Yuichi; TOCHIKUBO, Osamu; OHNO, Masato; SAWAI, Shinya; TAKEDA, Yuichi; SAWAI, Asuka; MOTOMURA, Takuma; FUJII, Hitoshi (Journal of Nutritional Science and Vitaminology, 2019)
Mental stress is a known risk factor for disease. This study investigated changes in sensations of taste and pungency before and after mental stress. Thirty healthy male university students rested for 20 min, performed mental arithmetic tasks for 10 min, and then underwent measurement of changes in their taste and ability to discern pungency. Taste was measured with the “Taste Disk®,” and pungency was measured by a filter-paper disc method using capsaicin solution. Subjects were not told the order of the reagent solutions used. To quantify pain sensation, a weak current applied to the central inner forearm skin by a Pain Vision® quantitative pain sensation analyzer was gradually increased. The degree of stress was measured by portable electrocardiography (ECG). During mental stress, the cognitive threshold of salty taste, sweet taste, and bitterness was significantly decreased, whereas the sensations of pungency and forearm skin pain were increased and showed significant correlation. Based on sympathetic nerve activity analyzed with the ECG, the subjects were divided into the mental stress group and non-mental stress group. The mental stress group experienced an increase in the pungency threshold and sensation of forearm skin pain with significantly high correlations obtained, whereas no correlation was found between these factors in the non-mental stress group. Acute mental stress increased the sensitivity to taste but decreased the sensitivity to the sensation of pungency on the tongue and pain on the skin. Sympathetic activity activated by stress may affect taste and the sensation of pungency.